Pengaruh Motivasi Kerja Terhadap Pengembangan Soft Skill Preseptor Dalam Pembelajaran Praktek Klinik - Rosalinna Rosalinna; Asti Andriyani (Poltekkes Kemenkes Surakarta, 2018)
Abstract: Motivation, Preceptor, Softskills. As a vocational education, midwifery institutions educate students' skills largely through the process of clinical practice learning. The need for soft skills in today's workplace is not negotiable, including midwife skills in working with health care institutions. The purpose of this study was to determine the effect of work motivation on the development of soft skills Preseptord in clinical practice learning. The method used in this research is quantitative with survey design. Population in this research are all midwives who work in RS Karanganyar and RS Sragen. Samples in this research is midwife who work in Maternity Room of Karanganyar Hospital and Sragen Hospital. The analysis of this study used chi square test and multiple logistic regression. The result of this research shows that there is influence of work motivation toward the development of soft skills of Preseptord in clinical practice learning (p value = 0,017) and POR = 9,000. Multivariate analysis of motivational influence controlled by characteristic variable (age, education, duration of work and training) showed that motivation and duration significantly influenced the development of soft skill of preceptor (ρ value = 0,011) and POR Adjusted = 2,546. Further analysis shows the influence of motivation with every aspect of soft skill (discipline, responsibility, communication and cooperation (ρ value <0.05). Conclusion: work motivation influences the development of soft skills (discipline, responsibility and cooperation) of preceptor in clinical practice learning.